The war on hTG2: warhead optimization in small molecule human tissue transglutaminase inhibitors. Issue 2 (4th January 2023) - Mader, Lavleen; Watt, Sarah K. I.; Iyer, Harish R.; Nguyen, Linh; Kaur, Harpreet; Keillor, Jeffrey W.
Abstract : This systematic structure–activity relationship study provides key insights into warhead design and application for optimizing efficiency, selectivity, and pharmacokinetic stability of hTG2 inhibitors. Abstract : Human tissue transglutaminase (hTG2) is a multifunctional enzyme with protein cross-linking and G-protein activity, both of which have been implicated in the progression of diseases such as fibrosis and cancer stem cell propagation when dysregulated, prompting the development of small molecule targeted covalent inhibitors (TCIs) possessing a crucial electrophilic 'warhead'. In recent years there have been significant advances in the library of warheads available for the design of TCIs; however, the exploration of warhead functionality in hTG2 inhibitors has remained relatively stagnant. Herein, we describe a structure–activity relationship study entailing rational design and synthesis for systematic variation of the warhead on a previously reported small molecule inhibitor scaffold, and rigorous kinetic evaluation of inhibitory efficiency, selectivity, and pharmacokinetic stability. This study reveals a strong influence on the kinetic parameters k inact and K I with even subtle variation in warhead structure, suggesting that the warhead plays a significant role in not only reactivity, but also binding affinity, which consequently extends to isozyme selectivity. Warhead structure also influences in vivo stability, which we model by measuring intrinsic reactivity with glutathione, as well as stability in hepatocytes and in whole blood, giving insight into degradation pathways and relative therapeutic potential of different functional groups. This work provides fundamental structural and reactivity information highlighting the importance of strategic warhead design for the development of potent hTG2 inhibitors.